Absence of the musculocutaneous nerve: a rare anatomical variation with possible clinical-surgical implications - Fregnani, José Humberto Tavares Guerreiro; Macéa, Maria Inez Marcondes; Pereira, Celina Siqueira Barbosa; Barros, Mirna Duarte; Macéa, José Rafael (São Paulo Medical Journal, 2008)
CONTEXT: The musculocutaneous nerve is one of the terminal branches of the lateral fasciculus of the brachial plexus, and is responsible for innervation of the fl exor musculature of the elbow and for skin sensitivity on the lateral surface of the forearm. Its absence has been described previously, but its real prevalence is unknown. CASE REPORT: A case of absence of the musculocutaneous nerve that was observed during the dissection of the right arm of a male cadaver is described. The area of innervation was supplied by the median nerve. From this, three branches emerged: one to the coracobrachialis muscle, another to the biceps brachii muscle and the third to the brachialis muscle. This last branch continued as a lateral antebrachial cutaneous nerve. This is an anatomical variation that has clinical-surgical implications, considering that injury to the median nerve in this case would have caused unexpected paralysis of the fl exor musculature of the elbow and hypoesthesia of the lateral surface of the forearm.